Legal Implications on Cancellation of Agreements Made Prior to Custody for Good Faith Land Buyers - Ghansham Anand; Dinda Silviana Putri; Xavier Nugraha; Julienna Hartono; Melati Ayu Pusparani (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2022)
This study aims to analyze the construction of the cancellation of the land purchase agreement and legal protection for the seller in land purchases before the custody. The study used statute, case, and conceptual approaches. It focuses on the concept of custody and good faith. After analyzing the relevant legal sources, it is known that, on the one hand, Article 447 of the Indonesian Civil Code allows for the retroactive application of the custody in some conditions: (1) the custody is due to unwise, mental disorder, and irrational; and (2) the reasons underlying the custody had existed at the time the legal action is taken. The implementation of Article 447 can cancel land purchases made before the custody. On the other hand, the state must protect the buyer’s principle of good faith even though the seller is an unauthorized person. Article 447 must be applied because (1) the Indonesian Civil Code is a positive law that must be enforced; (2) people who are placed under custody are more at risk of experiencing losses in land purchases, and (3) construction of good faith land buyers cannot be applied because there are fewer parties.DOI: https://doi.org/10.22304/pjih.v9n2.a6